Strategi Pemasaran melalui Penerapan Services Marketing untuk Meningkatkan Kepuasan Pelanggan RAM Sawit di Ridan Permai - Rika Duri; Samsurijal Hasan; Rinda Fithriyana (Lembaga Pengembangan Kinerja Dosen, 2025)
Businesses must use efficient marketing techniques to match consumer expectations in the highly competitive palm oil sector. Determining the effect of service marketing methods on customer satisfaction is the goal of this study. Quantitative research using an experimental design is the methodology employed. A basic random sampling approach was used to identify the 109 farmers that sell their palm oil to RAM Sawit for the research sample. Questionnaires measuring different facets of customer satisfaction and service marketing were used to collect data. With a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.673, the findings indicate a significant link between customer happiness and service marketing. At RAM Sawit in Ridan Permai, when effective service tactics are implemented to satisfy customer expectations and raise customer happiness, service marketing may increase customer contentment. In conclusion, the effective implementation of service marketing strategies has great potential to increase customer satisfaction at RAM Sawit in Ridan Permai, and the company must continue to innovate and improve service quality to maintain competitiveness in the market. The suggestion from this research is that companies continue to innovate in services, improve communication with customers, and maintain service quality in order to build long-term loyalty and expand market reach.